2021
DOI: 10.1007/s10804-021-09383-3
|View full text |Cite
|
Sign up to set email alerts
|

A Drive for Redemption: Relationship Quality as a Mediator Linking Childhood Maltreatment to Symptoms of Social Anxiety and Depression

Abstract: Childhood maltreatment is associated with mental health problems across the life course and depression and social anxiety are two of the more common problems. Given the interpersonal nature of childhood maltreatment, adult romantic relationships have also been a keen interest. It has been suggested that the interpersonal relationships may mediate the relationship between maltreatment and adult mental health; however, little research has examined the mediating role of adult romantic relationships. This omission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Adults who experienced more severe maltreatment in childhood also reported that their contemporary relationships with family members are more strained and less supportive, which then increase adults' future perceptions of stress. Adults who were maltreated may be angry and resentful a (Fitzgerald & Williams, in press) and they behave in congruent ways. For example, childhood maltreatment is associated with being more critical of family members in adulthood (Fitzgerald & Morgan, 2022) and this may lead to less frequent contact and less support (Kong et al, 2019; Kong & Moorman, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adults who experienced more severe maltreatment in childhood also reported that their contemporary relationships with family members are more strained and less supportive, which then increase adults' future perceptions of stress. Adults who were maltreated may be angry and resentful a (Fitzgerald & Williams, in press) and they behave in congruent ways. For example, childhood maltreatment is associated with being more critical of family members in adulthood (Fitzgerald & Morgan, 2022) and this may lead to less frequent contact and less support (Kong et al, 2019; Kong & Moorman, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Data for the current study were drawn from MIDUS 2 (family support, family strain, and the covariates), MIDUS 2 biomarker (child maltreatment, stress, and sleep quality), and MIDUS 3 (number of chronic health conditions). Although maltreatment was measured at the second wave, given the retrospective nature and the weaknesses of the MIDUS 1 measure of maltreatment (see Fitzgerald, 2022b for a more detailed discussion), it was evaluated to be of minimal threat to the reliability and validity of the results. Data are publicly available and deidentified, thus IRB approval was not required.…”
Section: Methodsmentioning
confidence: 99%
“…Further, these claims have been found using both cross-sectional (Dunlop et al, 2015) and longitudinal research (Colman & Widom, 2004; DiLillo et al, 2009). Further, the associations between childhood maltreatment and adult romantic relationships are based on a dose-response relationship where a greater “dose” of childhood maltreatment is inversely associated with the quality of adult romantic relationships, or “response” (Dube et al, 2005; Fitzgerald, 2022; Scott-Storey, 2011). Childhood maltreatment is a form of interpersonal trauma that is either an act of omission (e.g., neglect), where children do not get their physical or emotional needs met, or commission (e.g., abuse), where they are victims of acts that cause emotional or physical harm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the seminal Adverse Childhood Experiences (ACE) study (Felitti et al, 1998) found a dose-response relationship between childhood maltreatment and other forms of childhood adversities, and adult mental and physical health outcomes. More recently, other studies have considered a dose-response relationship between childhood maltreatment and adult mental and relational outcomes (Arata et al, 2005; DiLillo et al, 2007; Fitzgerald, 2022; Handley et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although several studies have implied the role of traumatic family experiences in SAD (Binelli et al, 2012;Bruijnen et al, 2019), the association of humiliation as an independent factor that occurs mostly in relationships with peers and early life experience that are not necessarily traumatic have not been explored. So also studies have suggested the role of traumatic experiences in the formation of social anxiety (Fitzgerald, 2021;Fitzgerald & Gallus, 2020;Shahar et al, 2015), but early life experiences that are not necessarily traumatic, such as discrediting emotions in childhood and the mechanism of action based on the emotion-focused treatment model, have not been studied.…”
Section: Literature Reviewmentioning
confidence: 99%